Benzylidenecyclohexanone-triazole-based conjugated polymer: Click synthesis, Staudinger end-capping and application as optical probe scaffold. (October 2016) - Shi, Wei; Xu, Linxian; Xie, Zhengfeng; Chen, Xin
Abstract: A type of benzylidenecyclohexanone-triazole based conjugated polymer (P5 ) was successfully synthesized by Cu + -catalyzed Click reaction. The THF solution ofP5 exhibited specific optical response (increase in absorption and decrease in fluorescence) toward I − . With the further addition of Hg 2+ into the assembly ofP5 -I −, distinctive recovery of optical properties was detected, suggests thatP5 -I − adduct can act as fluorescence turn-on probing platform for Hg 2+ . Post-polymerization ofP5 was implemented by catalyst-free Staudinger reaction betweenP5 and triphenylphosphine to afford phosphinimine-endcapped polymer (P5-TPP ). Different from the blue-greenish emission (∼490 nm) ofP5, P5-TPP emitted yellow light (∼550 nm) in THF–water mixture (VTHF /Vwater = 2/8).P5-TPP displayed specific fluorescence ratiometric alteration toward hypochlorite ion in THF–water mixture (VTHF /Vwater = 2/8, pH = 7.4), which might be due to the hypochlorite-induced hydrolysis of phosphinimine energy-transfer acceptors inP5-TPP . The results suggest thatP5 can act as structure scaffold for the construction of optical probe for triple analytes (I −, Hg 2+ and ClO − ). Graphical abstract: Highlights: Benzylidenecyclohexanone-triazole based conjugated polymer (P5 ) was synthesized. Fluorescence ofP5 was specifically quenched by the introduction of I − . Fluorescence turn-on probing of Hg 2+ was achieved byP5 /I − assembly. Phosphinimine-endcapped polymer (P5-TPP ) was obtained by Staudinger reaction. P5-TPP displayed fluorescence ratiometric alteration toward hypochlorite ion.